(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Sometime in 1970, I had a conversation with a retired expatriate pathologist, working in the Ministry of Health, Kenya on contract. On learning that I was a new lecturer in pharmacology, University of Nairobi, he volunteered his views on the subject. I learnt that he was an alumnus of Cambridge University, England. A quick mental calculation placed him in his early 60s, which meant he had studied medicine in Cambridge in the 1930s, long before the first antibiotic, penicillin, was put to clinical use. He complained that he found pharmacology a difficult subject during his undergraduate studies. Needless to say, what he was calling pharmacology was “materia medica”, a study of material and substances used in medicine, their names, sources, physical characteristics and chemical properties, their preparations and dosages. He could recall such drugs as “tincture of digitalis”, “belladonna with antacids” and “Ipecacuanha”. A quick review of literature shows that the majority of drugs (over 95%) were discovered after 1950. So what did the learned doctor study at Cambridge?